La e-santé en prison - Ulysse Py (Netcom)
The research intend to question the current and potential benefits of increasing the use of telehealth for persons deprived of their liberty. These benefits can be of several kinds, health, economic, organizational and social. But risks also exist (patients’ rights, weakening of the care relationship, data security). The question of the benefit-risk balance arises in fact for persons deprived of liberty, as patients, but it will also arise for health professionals, prison administration or for the State, particularly with regard to public health.